2018
DOI: 10.30544/294
|View full text |Cite
|
Sign up to set email alerts
|

A preliminary investigation on microstructure and mechanical properties of dissimilar Al to Cu friction stir welds prepared using silver interlayer

Abstract: Due to its solid-state nature, friction stir welding (FSW) process can be considered a better alternative for dissimilar welding metals. However, like fusion welding techniques, in friction stir welding growth of thick layers of brittle intermetallics -Cu9Al4 and CuAl2 is a significant issue. One solution to this problem is the use of the suitable interlayer material. Use of interlayer material modifies the joint microstructure with the replacement of thick, brittle intermetallics by more ductile intermetallic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
19
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(19 citation statements)
references
References 14 publications
(23 reference statements)
0
19
0
Order By: Relevance
“…When Al-Cu is welded without interlayer either through butt configuration or lap configuration, the IMCs formed are AlCu, 2,7,11,16,20,22,26 Al 2 Cu, 2,7,11,16,[20][21][22]26,110,111,113,114 Al 2 Cu 3 , 7,11,20,22,112 Al 3 Cu 4 , 20,22 and Al 4 Cu 9 . 7,11,12,16,20,22,26,109,[111][112][113][114] Mechanical properties of FSWed Al-Cu joints Sahu et al investigated the hardness of dissimilar friction stir welded Al-Cu joints. They reported that the bottom layer's hardness was higher than the upper and middle layers, as well as the thickness of the weld, due to the faster cooling rate and the presence of different IMCs.…”
Section: Microstructures and Imcsmentioning
confidence: 99%
See 4 more Smart Citations
“…When Al-Cu is welded without interlayer either through butt configuration or lap configuration, the IMCs formed are AlCu, 2,7,11,16,20,22,26 Al 2 Cu, 2,7,11,16,[20][21][22]26,110,111,113,114 Al 2 Cu 3 , 7,11,20,22,112 Al 3 Cu 4 , 20,22 and Al 4 Cu 9 . 7,11,12,16,20,22,26,109,[111][112][113][114] Mechanical properties of FSWed Al-Cu joints Sahu et al investigated the hardness of dissimilar friction stir welded Al-Cu joints. They reported that the bottom layer's hardness was higher than the upper and middle layers, as well as the thickness of the weld, due to the faster cooling rate and the presence of different IMCs.…”
Section: Microstructures and Imcsmentioning
confidence: 99%
“…Al, and this, along with the Al matrix, forms a composite structure. 12 In an effort to reduce the production of Al-Cu intermetallics, Pandya and Menghani electroplated a thin layer (nearly 15 µm) of pure Zn on the abutting edge of pure Cu sheets before welding. However, at extremely high heat input, intermetallic production was still inevitable.…”
Section: Types Of Interlayersmentioning
confidence: 99%
See 3 more Smart Citations